MEMINIMALISASIKAN KASUS PENCEMARAN NAMA BAIK MENGGUNAKAN PENERAPAN ASAS SEBAB AKIBAT DALAM BIDANG SARANA ELEKTRONIK - Putri Adintya; Meli Tania S (Gapenas Publisher, 2023)
Technological advances have increased the occurrence of Cyber Crime in the form of defamation in the field of electronic means. In the case of defamation, it can contain the principle of cause and effect or conditio sine qua non, that is, there is an action that is the cause of the realization of a criminal act of defamation. This principle has the disadvantage that it has implications for the possibility of conviction of people who should not be convicted. Apparat currently still provides criminal sanctions under the ITE Law, so it can be detrimental if defamation turns out to be ignited by unpleasant treatment from others. This article aims to analyze efforts to minimize defamation using the application of the principle of cause and cause in the field of electronic means. This article uses normative legal research methods using secondary data obtained by means of literature studies, which are then analyzed qualitatively. The results showed that to minimize the occurrence of criminal defamation cases in electronic means can be done by being careful and wise in issuing statements orally and in writing. Then all information to be published must have received permission from the person concerned. Because in defamation cases, the apparat does not see any principle of causation so that everyone who commits insulting words can be a suspect, even if the motive is self-defense or merely shedding annoyance